Antidiabetic Activity of the Methanol Fraction of Sungkai Leaves (Peronema canescens Jack) - Indra Lasmana Tarigan; Anggi Ayunda Triani; Madyawati Latief (Chemistry Department, The University of Brawijaya, 2023)
Diabetes Mellitus (DM) is one of a group of metabolic diseases characterized by hyperglycemia caused by a disturbance in insulin so that blood glucose levels increase. Prevention of absorption of blood glucose by the intestine can be done with the help of the enzyme α-glucosidase. Based on the results of phytochemical tests, it is known that the methanol fraction of sungkai leaves contains flavonoid compounds. The Fourier Transform Infra-Red (FTIR) spectrum showed that the isolates had phenolic O-H groups (3,354.53 cm-1, 1,359.28 cm-1), aromatic C=C group (1,615.48 cm-1), C-O-C ether group (1,046.60 cm-1) and aromatic C-H group (822.21 cm-1). In vivo antidiabetic activity test was carried out using test animals of white male mice which were induced by alloxan. Antidiabetic testing was carried out using 6 treatment groups with glibenclamide, Na-Carboxymethyl cellulose (Na-CMC) 0.5%, dose 175 mg/kgBW, 350 mg/kgBW, 700 mg/kg Body Weight (BW) and isolates 2 mg/kgBW. The results showed that the methanol fraction of sungkai leaves had the best antidiabetic activity at a dose of isolate and 700 mg/kgBW which was able to reduce blood glucose levels by 42.20% and 42.00%. In vitro antidiabetic testing through α-glucosidase enzyme inhibition mechanism did not show any antidiabetic activity at concentrations of fractions 5, 10, 25, 50 and 100 ppm.